2017
DOI: 10.2135/cropsci2016.08.0704
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield and Nitrogen Accumulation in Maize Hybrids Released during 1934 to 2013 in the US Midwest

Abstract: Nitrogen (N) application in maize (Zea mays L.) reached a maximum of 145 kg N ha−1 in the US Midwest in 1975. Grain yield has continued to increase at a rate of 111 kg ha−1 yr−1, implying an improvement in N efficiency. Our objective was to measure the rate of genetic gain and the traits that contributed to the observed N efficiency for a set of DuPont Pioneer hybrids released between the era decades (ERA) of 1934 to 2013. These hybrids represent the most widely sold hybrids (by volume) in each ERA. A randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 34 publications
(115 reference statements)
12
55
1
Order By: Relevance
“…Applied fertilizer NUE has been measured between 15 and 85% due to crop, climate, soils, cultural practices, and a host of other factors but typically averages between 30 and 50% (Tilman et al, 2002). DeBruin et al (2017) and others have demonstrated increases in maize NUE due to improved genetics and other factors. However, higher yielding hybrids have been found to be less yield stable at high N rates than under low N conditions due to genotype × environment interactions (Mastrodomenico et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%
“…Applied fertilizer NUE has been measured between 15 and 85% due to crop, climate, soils, cultural practices, and a host of other factors but typically averages between 30 and 50% (Tilman et al, 2002). DeBruin et al (2017) and others have demonstrated increases in maize NUE due to improved genetics and other factors. However, higher yielding hybrids have been found to be less yield stable at high N rates than under low N conditions due to genotype × environment interactions (Mastrodomenico et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%
“…The optimum plant population depends on several crucial factors, including soil fertility, soil water-holding capacity, and hybrid maturity group (Sangoi et al, 2002). Interactions between plant genotype and plant population can also affect maize grain yield, with a recent study conducted by DeBruin et al (2017) finding a positive…”
Section: Research Scientific Perspectivesmentioning
confidence: 99%
“…In recent decades, maize grain yields improved with unchanged N inputs, clearly showing more effective N use by modern hybrids (Duvick, 2005;DeBruin et al, 2017). The application rate and timing of N may be altered by the producer according to the prevailing soil and environmental conditions.…”
Section: Soil Tillage and Crop Managementmentioning
confidence: 99%
“…Genotypic and environmental variations in the timing and partitioning of N accumulation in maize has been reported (Beauchamp et al, 1976;Moll et al, 1982;Ma and Dwyer, 1998). The period of most rapid N accumulation occurs from V10 to V14 (DeBruin et al, 2017). However, low soil N availability early in the growing season can delay the timing of maximum N accumulation rate (Russelle et al, 1983;Massignam et al, 2009).…”
Section: Core Ideasmentioning
confidence: 99%